Frailty levels in non-institutionalized older adults and sociodemographic characteristics - Quintero-Cruz, María Victoria; Herazo-Beltrán, Yaneth; Terán-Martínez, Miguel; Viecco-Montero, Lay; Coronel-Verdecia, Alexander; Villegas-Padilla, Yecid; Cure Manchego, Jorgina (Gaceta Médica de Caracas, 2021)
Introduction: Frailty in older adults is a public health challenge and a priority, given its effects on the functional decline of individuals. Several factors account for its occurrence, including individual aspects. Purpose: To determine frailty levels and their association with sociodemographic characteristics in non-institutionalized older adults.